Understanding a Developer Social Network and its Evolution - Hong, Qiaona; Kim, Sunghun; Cheung, S. C.; Bird, Christian (Proceedings of the 27th IEEE International Conference on Software Maintenance, 2011)
With the increase of large scale software projects, software development and maintenance demand the participation of a group of developers instead of individuals. Therefore having a thorough understanding of the group of developers is critical in terms of improving development and maintenance quality and reducing cost. In contrast to most commercial software endeavors, developers in open source software (OSS) projects enjoy more freedom to organize and contribute to a project in their own working style. Their interactions through various means in the project generate a latent developer social network (DSN). We have observed that developers and their relationships in these DSNs change continually under the influence of differences in the set of active developers and their changing activities. Revealing and understanding the structure and evolution of these social networks as well as their similarities and differences from other more general social networks (GSNs) is of value to our software engineering community, as it allows us to begin building an understanding of how well the findings from other fields based on GSNs apply to DSN. In this paper, we compare DSNs with popular GSNs such as Facebook, Twitter, Cyworld (a large social network in South Korea), and the Amazon recommendation network. Interesting results were found. For instance, while most social networks exhibit power law degree distributions, our DSNs do not. In addition, we also examine how DSNs evolve over time, highlighting how events within a project (such as a release or the departure of prominent developers) impact the makeup of the DSNs, and observe the evolution of topological properties such as modularity and the paths of communities within these networks.